Review of Legal Decisions on the Protection of Human Rights of Indonesian Football Supporters in a Juridically Normative Way - Raihan Fakhri Ramadhan; Muhammad Hatta Hakim; Bagus Adrianto (Indonesian Journal of Sports Law, 2024)
The need for human rights protection remains a fundamental issue. Therefore, justice in the implementation of human rights is supported by a juridical-normative approach. This is to ensure justice for every individual, regardless of their status or group. However, this has not received a sufficiently positive response in several human rights violation cases. One example is the human rights violation case involving football supporters in Kanjuruhan in 2022. The perceived inadequate response is reflected in reports stating that the charges against the suspects did not result in fair sanctions. This has led to statements of insensitivity towards the effects suffered by the victims of the football tragedy. Therefore, it is crucial to analyze, both generally and specifically, the justice received by the football supporters in the Kanjuruhan tragedy of 2022 using a Juridical-Normative approach accompanied by a qualitative method. The analysis process uses primary data, including journalistic reports related to the tragedy and various human rights laws. Secondary data is obtained from several other journals. From this research, it was concluded that, in general, the defendants in the Kanjuruhan supporter case were subjected to criminal law. This is based on the element of unintentionality and the fact that the defendants still have human rights equivalent to those of the supporters. As a result, the supporters have received their rights, even though there are still statements of insensitivity, and the law is enforced, albeit with some overlap. Subsequently, this issue becomes an evaluation for various parties involved in event management, particularly security personnel. The hope is that such incidents will not recur in the future, while still upholding human rights values